Electronic documents: Reflections on information professionals´ relationships with technology. Part II - Bustelo-Ruesta, Carlota (Anuario ThinkEPI, 2008)
This is the second part of the analysis of the complex relationships between information technologies and information professionals in an environment in which, for the first time, standards and legislation are ahead of implementation. An example is the different interpretations on how to apply the Spanish "Law on electronic access of citizens to public services" to electronic records management. The idea that digital signatures should be preserved indefinitely with the electronic records presents an unnecessary technological complexity, when other solutions exist.